The relationship between teachng quality factors and professional development of academics at UAE higher education - Elatawneh, Hebah Ahmad Ali (2022)
Quality in higher education has become the emphasis of all institutions of higher education due to the competitive market of higher education and the need to prepare graduates relevant to the global market. Hence, attention need to be given to the quality of teaching in higher education. Additionally, there is a need to relook the conceptualization of quality teaching due to the lack of consensus and its complexity. As such, this research propose a conceptualization of quality teaching contextualized within higher education of the UAE, which is framed by four interconnected concentric circles, namely the individual teaching practices, academic professional identity, structures (policy) of HEIs and globalization and internationalization discourses. This model includes seven factors: five factors are categorised as academic competencies which are lesson design, teaching skills, communication skills, technology skills, and content expert; academic identity is represented by individual and occupational identity and contextual environment, represented by policy and strategy. Further, seven hypotheses were formulated to test the relationship of these factors to academic professional development. To validate and test empirically the model, a survey research has been conducted with academics in top three public universities in the UAE. Employing a simple randomised sampling method, a total of 283 samples were analysed through descriptive statistical analysis and Structural Equation Method. It was found that communication skills and lesson design were the two highest factors, followed by policy and strategy. While technology skills were the least important factor among the seven factors of quality teaching. All the five factors of academic competence were found to have significant relationship with academic professional development, while the contextual and identity factors did not have significant relationship with the academic professional development. The model of quality teaching of this research considers the role of contextual environment in influencing quality teaching. This model consists of academics’ competencies and contextual environment. This research is valuable for academics, management of higher education as well as government to plan strategically for development of academic competency in delivering quality teaching in higher education.